Microwave-assisted synthesis of Zeolite-based catalysts for pyrolysis of Lignocellosic biomass - Nyembe, Nhlanhla (University of the Witwatersrand, Johannesburg, 2025)
This work evaluated blast furnace slag as a potential industrial waste resource for zeolite synthesis. The primary objective of employing blast furnace slag was to develop a sustainable downstream beneficiation process for the iron and steel manufacturing industry to curb its impact on the environment. This entailed the beneficiation of the slag for the removal of impurities (Ca and Mg), the use of the pretreated slag as a silicon and aluminum precursor for the synthesis of ZSM-5, and the catalytic evaluation of the synthesized ZSM-5 for the conversion of lignocellulosic biomass (corn cob) into bio-oil. The major compounds found in the slag waste were Al2O3 (16.1 wt.%), CaO (30.6 wt.%), SiO2 (35.1 wt.%), and MgO (10.5 wt.%). The slag waste was pretreated using acid leaching to reduce the concentration of CaO and MgO to 4.83 wt.% and 2.54 wt.%, respectively. The optimal acid leaching conditions resulted in a leaching efficiency of 71.1% and 80.4% for Mg and Ca, respectively. The maximum leaching efficiencies were achieved using the following optimum leaching conditions: solids concentration of 8 wt.%, leaching time of 90 min, and HCl concentration of 3 mol/L. Morphological analysis of the raw and pretreated slags revealed that both slags consisted of irregular-shaped stonelike formations with diverse particle sizes and fibrous surfaces. However, the mineral composition was found to be akermanite for the raw slag and augite for the pretreated slag. A comparative study was conducted by utilizing both slags (raw and pretreated) in the synthesis of zeolitic materials, and it was found that the concentration of CaO and MgO in the starting material significantly affected the zeolite synthesis process. Therefore, the microwave-assisted hydrothermal synthesis technique was used to convert the pretreated slag into ZSM-5. It was observed that the synthesis temperature significantly influenced the size of the crystals formed, whereas the synthesis time influenced the shape. The maximum synthesis conditions were found to be 13h and 180°C. The ZSM-5 obtained using the maximum conditions was found to consist of the major characteristic diffraction peaks similar to commercial ZSM-5. However, additional peaks observed were attributed to the presence of augite in small quantities. The synthesized ZSM-5 consisted of well-defined cubic prism shapes with small intergrown rectangular crystals. Furthermore, the morphology of the crystals changed as the synthesis time was varied. The crystalline structure of the synthesized ZSM-5 was found to be mesoporous with moderate relative crystallinity (52.4%). The pore size was relatively high (14.8 nm) with a relatively low BET surface area (108.4 m2/g). The change in the synthesis conditions (time and temperature) did not affect the chemical composition of the resulting product. Corn cob residue used was obtained from farm-works and consisted of 75.98 wt.% of volatile matter, making them suitable as a biomass substrate. The synthesized catalyst was evaluated against the commercial catalyst for bio-oil conversion, with performance differences attributed to the presence of trace metal elements. The product distribution was significantly affected by varying the pyrolysis conditions, such as catalyst-to-biomass ratio, pyrolysis time, and pyrolysis temperature. The effect of pyrolysis conditions showed that an increase in pyrolysis temperature positively improved the bio-oil and gas yield. Since ZSM-5 is a bifunctional catalyst, a high catalyst-to-biomass ratio promoted deoxygenation, and a low catalyst-to- biomass ratio resulted in shape selectivity. The pyrolysis time had the least impact on the xiv product distribution. The maximum pyrolysis conditions were found to be 350°C, 3 min, and catalyst-to-biomass of 1:9. The primary product was bio-oil. However, the gas yield superseded that of the oil. Both catalysts (synthesized and commercial ZSM-5) had a selectivity towards phenols and ketones; however, their compositions varied significantly. The most prominent chemical compounds identified in each group were catechol and cresol for phenol and ethenone and cyclohexanone for ketone. The considerable presence of ketones and phenols in the bio- oil derived in this study exhibits the potential applicability of the synthesized catalyst (ZSM- 5) for the production of alternative fuels that mimic fossil fuels subsequent to the removal of oxygenates.
A research report submitted in fulfillment of the requirements for the Master of Science, in the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Acid leaching; Bio-oil; Biomass; Blast furnace slag; Crystallinity; Hydrothermal; synthesis; Mesoporosity; Microwave irradiation; Microwave pyrolysis; Zeolite; SDG-7: Affordable and clean energy; SDG-12: Responsible consumption and production